Morphological changes and DNA damage in Chlorella vulgaris (UMT-M1) induced by Hg2+ - Hazlina A.Z.,; Devanthiran L.,; Fatimah H., (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study reported the effects of Hg2+ on the morphology and DNA of a microalga, Chlorella vulgaris (UMT-M1). Morphological changes and DNA damage in cells were analysed using scanning electron microscope (SEM) and Comet assay, respectively. The half maximal inhibitory concentration (i.e. IC50 ) of Hg2+ on the growth of C. vulgaris obtained from the dose-response curve was 0.72 mg/L. Under SEM, it was observed that Hg2+ treated cells become smaller in size (i.e. 2.1±0.1 μm) compared to normal cells (i.e. 3.2±0.1 μm). The morphology of cells changed from an intact microalgal cells with smooth spherical surface to a slightly roughened surface and shrivelled shape. Apoptotic bodies were also observed under 0.001, 0.01 and 0.1 mg/L of Hg2+ but not in 1.0 mg/L Hg2+. These results indicate that Hg2+ may induce apoptotic cell death at low concentrations but not at the highest concentration of 1.0 mg/L. The highest percentage of cells with comet level of 4 was observed in 1.0 mg/L Hg2+. However, Hg2+ is genotoxic to the microalga even at low concentration. In conclusion, Hg2+ can exert its toxic effects on C. vulgaris by changing the microalgal morphology, damaging the microalgal DNA and inducing cell death in the microalgal cells using different pathways at different concentrations.